Public Perception of the Implementation of Simultaneous Regional Head Election 2020 during Covid-19 Pandemic in Palangka Raya Regency - Jhon Retei Alfri Sandi; Suprayitno Suprayitno; Imanuel Jaya (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Central Kalimantan is one of the provinces in Indonesia will implement the Regional Election simultaneously on December 9, 2020. There are 2 (two) Regional Elections, they are Governor and Deputy, and Mayor and Deputy in Kotawaringin Timur Regency. On December 2020, at least 270 Regions would participate to Regional Elections in Indonesia, including provincials, Regencies, and Cities. The democracy atmosphere implementation would be different from previous over the years due to COVID-19 Pandemic as its prediction. This research aims to disclose Palangka Raya Public Perceptions of Regional Election in Covid-19 Pandemic recently. Majority Respondents agree to implement the Regional Election in Palangka Raya on December 9. Furthermore, The Regional Election could be implemented by following the Protocol Health Procedures with safe and healthy against Covid-19.